Databases and their Employment in the Flipped Classroom Learning Environment at Saudi Universities - Elsigini, Waleed Tageldin; Yamani, Hanaa Abdulraheem (Journal of Education and e-Learning Research, 2020)
The use of technology in education has become an urgent necessity and is no longer a luxury. This is evident through the attachment of students to their tablets, mobile phones, and other forms of various technologies. Therefore, educational institutions, especially universities and higher education institutions, must think according to the age variables and their requirements by providing interesting and attractive educational environments that suit the interests of students. In this context, several strategies based on the employment of modern technology have appeared in the educational process, perhaps the most prominent of which is called the flipped classroom. This paper aims to introduce a proposed model for employing databases in the flipped classroom learning environment at Saudi universities, based on the integration between database and instructional design models where the transition to a flexible and effective virtual learning environment suits the growing and changing needs of students; it also reviews the concept of the flipped classroom and its features in improving the teaching and learning process, as well as reviewing the database concept, its components, characteristics, and roles in developing the educational system.